2011
DOI: 10.1007/s10029-011-0855-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term quality of life after hernioplasty using a Prolene hernia system in adult inguinal hernia

Abstract: In a regional training hospital, primary inguinal hernias were treated with low recurrence and few complications by use of the PHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…3,11,44,56 Polypropylene mesh has also been used in hernia repairs and patch augmentation for open rotator cuff repair. 8,57 The immediate advantages of polypropylene mesh are as follows: (1) it provides augmentation in case the fascia lata graft is too friable; (2) it provides sufficient tensile strength, which is important in the early period of superior capsule reconstruction; and (3) it can minimize graft elongation inward to avoid reconstructed capsule attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,44,56 Polypropylene mesh has also been used in hernia repairs and patch augmentation for open rotator cuff repair. 8,57 The immediate advantages of polypropylene mesh are as follows: (1) it provides augmentation in case the fascia lata graft is too friable; (2) it provides sufficient tensile strength, which is important in the early period of superior capsule reconstruction; and (3) it can minimize graft elongation inward to avoid reconstructed capsule attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the patients in this study were elderly patients, unlike some other studies 18 , with some other comorbidities, so the antibiotic prophylaxis and general anesthesia were justified. The antibiotic prophylaxis was the reason why we did not have wound infections 19 .…”
Section: Discussionmentioning
confidence: 88%
“…With this technique, we solved primary, bilateral and recurrent hernias and showed that this technique is applicable for all indirect inguinal hernias results, despite of some other studies in wich PHS for recurrent hernias were not used 18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Inguinal hernia most probably has been a disease ever since mankind existed [1] . In view of its existence in different kinds of animals, and in particular of primates, one can assume that already prehistoric human beings were affected with the disease [2] . Written proof of this statement became available from manuscripts and founds in Mesopotamian and Egyptian cultures.…”
Section: Introductionmentioning
confidence: 99%